The Influence of Online Games and Social Media on Student Learning Motivation Moderated by Self-Control - Muhamad Ilham Prima Putra; Zul Afdal (Universitas Muhammadiyah Enrekang, 2025)
Using self-control as a moderating variable, this study attempts to examine how social media and online games affect students' motivation to learn at Padang State University's Faculty of Economics and Business. Students' extensive usage of digital technology can affect their motivation to learn in both positive and negative ways. Since social media and online games are two of the most popular digital activities, it is critical to look at how they affect students' motivation for learning. This study employed a quantitative methodology, gathering information from current students at Padang State University's Faculty of Economics and Business via questionnaires. For data analysis, moderated regression techniques were employed. The findings demonstrated that playing online games significantly reduced motivation to learn, while social media exhibited varying effects depending on the intensity and purpose of use. It has been demonstrated that Self-control lessens social media's influence. and online gaming on learning motivation. Students with high levels of self-control were able to manage their use of online games and social media more wisely so as not to interfere with their learning motivation. These results